Confocal laser endomicroscopy for diagnosing lung cancer in vivo - Fuchs, Florian; Zirlik, Sabine; Hildner, Kai; Schubert, Juergen; Vieth, Michael; Neurath, Markus (European Respiratory Journal, 2013)
Confocal laser endomicroscopy is a novel endoscopic technique that may allow imaging of living cells in lung tissue in vivo. We assessed the potential of this technique for the detection of histology during screening bronchoscopy for lung cancer. 32 patients with suspected malignancies underwent bronchoscopy with endomicroscopy using acriflavine hydrochloride. Standardised areas and localised lesions were analysed by in vivo confocal imaging during bronchoscopy and biopsies were taken. Confocal images were graded and correlated prospectively with conventional histology from biopsies. Acriflavine hydrochloride yielded high-quality confocal images and strongly labelled airway epithelial cells. No side-effects were noted. 75 522 confocal images from 56 different locations were compared prospectively with histological data from biopsy specimens. Endomicroscopy allowed subsurface imaging with detailed analysis of cellular and subcellular structures. Neoplastic changes could be predicted with high accuracy (sensitivity 96.0%, specificity 87.1%, accuracy 91.0%). Confocal laser endomicroscopy with acriflavine is a novel diagnostic tool for the analysis of living cells during bronchoscopy and permits virtual histology of neoplastic changes in the airways with high accuracy. This technique may enable the rapid diagnosis of neoplasia during ongoing endoscopy in patients with suspected lung cancer. Copyright©ERS 2013.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Bronchoscopy; Endomicroscopy; In vivo imaging; Lung cancer